The effect of a virtual reality based intervention on processing speed and working memory in individuals with ADHD—A pilot-study - Cunha, Filipa; Campos, Sara; Simões-Silva, Vitor; Brugada-Ramentol, Victòria; Sá-Moura, Bebiana; Jalali, Hossein; Bozorgzadeh, Amir; Trigueiro, Maria João (Frontiers in Virtual Reality, 2023)
This study aimed to evaluate the effectiveness of a virtual reality based intervention in processing speed and working memory in students with ADHD symptomatology. A randomized experimental study was conducted, with a sample consisting of 26 adult participants recruited from the Escola Superior de Saúde do Politécnico do Porto. The participants were allocated into two groups: a passive control group and an intervention group that completed 10 sessions using virtual reality-based games from the Enhance VR app. The intervention included 6 games: Whack-a-mole, Shuffled, Assembly, React, Memory Wall and Maestro. The participants underwent pre- and post-intervention evaluations using the Southwestern Assessment of Processing Speed (SWAPS) and the Sequence of Letters and Numbers and Spatial Location of the Wechsler Adult Intelligence Scale - 3rd Edition - WAIS-III. Descriptive statistics were used to characterize the sample and a mixed ANOVA was used to test the effectiveness of the intervention. There was an improvement in the results of processing speed in the group exposed to the intervention (p<0.001) and the value of the interaction between intervention and time was also significant (p=0.004). There were no statistically significant differences between the participants' working memory in the different variables under study, except for the values of the Spatial location test in the experimental group that improved relative to the initial assessment (p=0.034). A virtual reality cognitive training intervention resulted in improvements on the processing speed measures, which was not found in the control group. Although we cannot make the same conclusions regarding working memory, these results suggest that the VR intervention resulted in progress in the experimental group, possibly influenced by the intervention, which should be verified in future studies with longer interventions.